2008
DOI: 10.3174/ajnr.a1396
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stress in Intracranial Self-Expanding Stents Studied Using Ultra-High-Resolution 3D Reconstructions

Abstract: BACKGROUND AND PURPOSE:Imaging of intracranial stents is constrained by resolution limits of current clinical imaging techniques providing insufficient visualization of deployment details and impeding its use for computational hemodynamic (CHD) simulations. The purpose of our study was to evaluate whether ultra-high-resolution MicroCT scans can illuminate detailed aspects of realistic in vitro stent deployment and serve as a reliable basis for CHD simulations of blood flow through selfexpanding intracranial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Nonetheless, these previous studies are useful to investigate how various stent characteristics such as strut dimensions, orientation, angle with respect to flow direction, length, and intrastrut surface area affect the flow and distribution of hemodynamic forces inside the stented artery. The present study employs ultra-high resolution MicroCT based geometric reconstructions of deployed stents, which have recently shown to provide accurate in-stent hemodynamics simulations in a study by our group (Benndorf et al, 2009). Two intracranial stents, the open-cell design NF3 and the closed-cell design Enterprise, were deployed in similar PTFE tubes with the purpose of assessing stent deployment and the effects of different stent designs on hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, these previous studies are useful to investigate how various stent characteristics such as strut dimensions, orientation, angle with respect to flow direction, length, and intrastrut surface area affect the flow and distribution of hemodynamic forces inside the stented artery. The present study employs ultra-high resolution MicroCT based geometric reconstructions of deployed stents, which have recently shown to provide accurate in-stent hemodynamics simulations in a study by our group (Benndorf et al, 2009). Two intracranial stents, the open-cell design NF3 and the closed-cell design Enterprise, were deployed in similar PTFE tubes with the purpose of assessing stent deployment and the effects of different stent designs on hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-high resolution CT (MicroCT) recently proved capable of providing a spatial resolution sufficiently high to allow insights into near-wall flow patterns and WSS at the strut level using an in vitro model (Benndorf et al, 2009). The current study analyzes blood flow through a stented ''vessel'' using such accurate reconstructions of in-vitro (polytetrafluoroethylene tube, PTFE) and ex-vivo (canine artery) deployed self-expanding intracranial stents.…”
Section: Introductionmentioning
confidence: 99%
“…Focal intimal hyperplasia is sometimes observed at the stent markers. Poor attachment of the end-markers to the vessel surface has been observed for both Neuroform and Enterprise and may induce low wall shear stress as a reason of intimal hyperplasia [25,41] . Similar eff ects are to be expected for Solitaire.…”
Section: Cells Not Connectedmentioning
confidence: 99%
“…Many studies of numerical simulation and in vitro flow visualisation by dye injection, laser Doppler velocimetry or particle image velocimetry (PIV), were conducted using idealised or patient-specific models to studied the flow alterations inside the aneurysms caused by stents (Canton et al 2005;Ohta et al 2005;Cebral and Lohner 2005a;Meng et al 2006;Appanaboyina et al 2008;Kim et al 2008;Liou et al 2008;Benndorf et al 2009;Tateshima et al 2009). Ohta et al investigated the flow patterns in bifurcated aneurysm models with non-Newtonian fluid assumption and found that dynamic viscosity increased near the dome of the aneurysm after stent placement (Ohta et al 2005).…”
Section: Introductionmentioning
confidence: 99%